Cultural Representation, Identity, and Meaning Shifts in Multilingual Poetry Translation: A Comparative Study of Indonesian, English, and Hubula: Penelitian - Friska Simatupang; Dwi Puspitosari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study investigates the representation of culture and identity in multilingual poetry through a comparative analysis of Indonesian poems and their English and Huwula translations. The study aims to describe the forms of cultural and identity representation, analyze how these elements are translated into English and Hubula, identify the shifts or changes in meaning that occur during the translation process, and examine the similarities and differences among the three language versions. This study employed a qualitative approach using a descriptive-comparative method. The data consisted of poems presented in Indonesian, English, and Huwula versions. The units of analysis included words, phrases, clauses, sentences, and stanzas containing cultural elements, identity, symbols, metaphors, values, and meaning shifts.The findings show that the poems represent various cultural elements, including spiritual values, education, social relationships, cooperation, hard work, perseverance, hope, gratitude, respect, and human aspirations for the future. Identity is represented through individual and collective expressions, social roles such as teachers and students, and particularly through local linguistic identity in the Hubula version. Symbols and metaphors, such as roads, crossroads, light, pens, and journeys, play an important role in constructing cultural and identity meanings. The analysis also reveals several translation shifts, including meaning preservation, addition, semantic expansion, semantic modification, omission, and changes in metaphorical imagery. Although the central meanings and major cultural values are generally preserved across the three language versions, differences occur because of translation choices and linguistic structures. The Hubula version provides the strongest representation of local identity through its distinctive vocabulary and linguistic forms, whereas the Indonesian and English versions provide broader accessibility. Overall, the study demonstrates that literary translation functions not only as a process of transferring language but also as a process of preserving, transforming, and reinterpreting cultural meanings and identities.